INDONESIA EFL TEACHERS’ REFLECTIVE THINKING AND THEIR TEACHING STYLES: EXPLORING POTENTIAL RELATIONSHIP (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Reflective thinking is an important factor that can affect a teacher's effectiveness when teaching in the educational setting. This study aims to investigate the relationship between reflective thinking of EFL teachers in Indonesia and their teaching styles. A descriptive-correlational design was employed in the quantitative research method, and a survey with fifteen EFL teachers from different Indonesian schools was used to collect data. With a correlation of 0.757 and a significance value (sig) of 0.001
Keywords: Correlation; Pedagogical Practices; Professional Development; Teaching Effectiveness